Tumor Stage and Substage Predict Cancer-specific Mortality After Nephrectomy for Nonmetastatic Renal Cancer: Histological Subtype-specific Validation - Nocera, Luigi; Collà Ruvolo, Claudia; Stolzenbach, Lara F; Wenzel, Mike; Tian, Zhe; Larcher, Alessandro; Capitanio, Umberto; Mirone, Vincenzo; Tilki, Derya; Chun, Felix K H; Kapoor, Anil; Shariat, Shahrokh F; et al. (European urology focus, 2022)
BACKGROUND: For patients with nonmetastatic renal cell carcinoma (nmRCC) treated with nephrectomy, prediction of cancer-specific mortality (CSM) by T stage and substage has not been validated for the separate histological subtypes. OBJECTIVE: To investigate the ability of pathological T stage and substage to predict CSM for patients with clear-cell, papillary, or chromophobe nmRCC treated with nephrectomy. DESIGN, SETTING, AND PARTICIPANTS: Using the SEER database for 2004-2016, we identified 87 149 patients with T1-4 N0/X M0 nmRCC treated with nephrectomy for the clear-cell (65 715; 75.4%), papillary (14 587; 16.7%), or chromophobe (6847; 7.9%) histological subtype. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Kaplan-Meier plots and Cox regression models were used to estimate CSM. RESULTS AND LIMITATIONS: For all three histological subtypes, patients with T1a-T3a disease exhibited more favorable CSM than patients with T3b-T4 RCC. For clear-cell RCC, there were clinically meaningful and statistically significant differences for virtually all intergroup comparisons among T1a-T3a stages. For papillary T1a-T3a RCC, clinically meaningful differences disappeared, although the statistical significance remained. For chromophobe T1a-T3a RCC, no clinically meaningful or statistically significant differences were observed. For all three histological subtypes, patients with T3b-T4 RCC exhibited virtually uniformly unfavorable CSM, with no clinically meaningful intergroup CSM differences. CONCLUSION: The use of T stage and substage for stratification of patients with nmRCC treated with nephrectomy revealed differences in CSM among T1a-T3a cases, but not T3b-T4. The magnitude of the CSM difference was greatest for clear-cell, intermediate for papillary, and marginal for chromophobe RCC. PATIENT SUMMARY: For patients with kidney cancer, the stage of their disease assessed after surgery on the affected kidney can predict how likely they are to die from their cancer. This prediction varies for different subtypes of kidney cancer.
Keywords: proporcionální rizikové modely; Kidney cancer; Oncological outcomes; TNM staging; Proportional Hazards Models; Survival; Carcinoma, Renal Cell; nádory ledvin; Nephrectomy; Kidney; karcinom z renálních buněk; Humans; nefrektomie; lidé; Renal cell carcinoma; Surveillance, Epidemiology and End Results database; Kidney Neoplasms; ledviny